Studying the Adaptive Capabilities of Imported Apple-Tree Cultivars in Lowland Conditions of the Republic of Armenia - Stepanyana, E. R.; Beketovskiyb, D. A.; Mukhsyana, M. M.; Abrahamyana, A. A. (ՀԱԱՀ հիմնադրամ)
To study the adaptive and acclimatization capabilities of imported apple cultivars to expand the geographical boundaries of their use in the specific lowland conditions of the Ararat Valley as well as to understand their genetic resources in new growing conditions, production experiments were set up. The following encouraging data were obtained Based on a two-year study of five new novel cultivars of apple trees in three different areas. Five apple tree cultivars were investigated: Granny Smith, Jonagold Decosta, Fuji, Mutsu, and Gala. During observation and study, they showed a high yield productivity. As a result, all five imported cultivars of apple trees are recommended for growing in intensive orchards and under similar agro-climatic conditions.
Keywords: Agronomy and Agroecology